The Effable and the Ineffable The Linguistic Boundaries of Metaphysical Realism - Yannaras, Christos (Winchester University Press, 2022)
'What is the criterion of truth?', asks Christos Yannaras in The Effable and The Ineffable: The Linguistic Boundaries of Metaphysical Realism. Christos Yannaras is a Greek philosopher, Eastern Orthodox theologian and author of more than fifty books which have been translated into many languages. He is a professor emeritus of philosophy at the Panteion University of Social and Political Sciences, Athens. Of The Effable and The Ineffable, Archbishop Rowan Williams says: 'Christos Yannaras is one of the most original and revolutionary thinkers of modern Europe, and in this arresting, demanding book he sets out his vision of how a post-truth society might rediscover the reality of shared meaning and the hope of authentic life. Bringing the Greek Fathers into dialogue with the foremost thinkers of modernity, he gives us a comprehensive picture of what "logos" really means and why it matters.' Rowan Williams The Effable and The Ineffable: The Linguistic Boundaries of Metaphysical Realism is a title in the Winchester Modern Orthodox Dialogues. Modern Orthodox Dialogues examine the theological and cultural conversations currently taking place within the Orthodox Christian world. Modern Orthodox Dialogues also examine conversations between Orthodox Christianity and Western Christianity. The series aims to facilitate additional conversations and avenues of communication between the East and the West. For this reason, the series presents and highlights established Orthodox Christian thinkers whose thought is not known in the West. Winchester Modern Orthodox Dialogues promote new approaches and new voices to contribute to continuing conversations within Christianity. The Dialogues are edited by Andreas Andreopoulos.